Penyaluran Kredit Bank Umum di Indonesia Ditinjau dari Risiko Kredit dengan Profitabilitas Sebagai Mediasi - Raden Bagus Faizal Irany Sidharta; Abdurrahman Abdurrahman; Isra Dewi Kuntary Ibrahim (Riset, Ekonomi, Akuntansi dan Perpajakan (Rekan), 2021)
This research was aimed at finding to analyze the effect of credit risk on profitability, to analyze the effect of credit risk on credit allocation, to analyze the effect of profitability on credit allocation at commercial banking in Indonesia. The method of analyze was path analysis by smart PLS. Our empirical results showed that credit risk had a negative and significant effect to profitability, credit risk did not have significant effect to credit allocation, profitability had a positive significant effect to credit allocation and also credit risk had a negative effect on credit allocation through profitability at commercial banking in Indonesia